Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1109/access.2022.3182055
|View full text |Cite
|
Sign up to set email alerts
|

A Real-Time CNN-Based Lightweight Mobile Masked Face Recognition System

Abstract: Due to the global spread of the Covid-19 virus and its variants, new needs and problems have emerged during the pandemic that deeply affects our lives. Wearing masks as the most effective measure to prevent the spread and transmission of the virus has brought various security vulnerabilities. Today we are going through times when wearing a mask is part of our lives, thus it is very important to identify individuals who violate this rule. Besides, this pandemic makes the traditional biometric authentication sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…They found that the face recognition rate for identified students reached 77%, while the false-positive rate was reported at 28%. Kocacinar et al [7] developed a mobile system in realtime for recognizing masked faces using deep learning models, achieving a 90.40% validation accuracy. This system identifies full faces as well as just the eyes.…”
Section: Related Workmentioning
confidence: 99%
“…They found that the face recognition rate for identified students reached 77%, while the false-positive rate was reported at 28%. Kocacinar et al [7] developed a mobile system in realtime for recognizing masked faces using deep learning models, achieving a 90.40% validation accuracy. This system identifies full faces as well as just the eyes.…”
Section: Related Workmentioning
confidence: 99%
“…In [192], a DTL-FMD is introduced by fine-tuning a MobileNetv2 base model with the imageNet weights and adding a new fully-connected head to process input data for analysis. Finally, in [193], a real-time CNN-Based lightweight mobile FMD system is proposed. Three different pre-trained models, including VGG16, MobileNet, ResNet50 are fine-tuned to enhance the detection performance.…”
Section: Fmd Based On Deep Transfer Learning (Dtl)mentioning
confidence: 99%
“…By utilizing a mobile application named MadFaRe [ 14 ], the authors suggested and verified a technique to discriminate between masked, unmasked, and incorrectly masked persons. Eight object detection models and four face detection models make up the Adhikarla and Davison [ 10 ] framework.…”
Section: Related Workmentioning
confidence: 99%